2011
DOI: 10.1371/journal.pone.0021926
|View full text |Cite
|
Sign up to set email alerts
|

Orally Active Multi-Functional Antioxidants Are Neuroprotective in a Rat Model of Light-Induced Retinal Damage

Abstract: BackgroundProgression of age-related macular degeneration has been linked to iron dysregulation and oxidative stress that induce apoptosis of neural retinal cells. Since both antioxidants and chelating agents have been reported to reduce the progression of retinal lesions associated with AMD in experimental animals, the present study evaluates the ability of multi-functional antioxidants containing functional groups that can independently chelate redox metals and quench free radicals to protect the retina agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
(71 reference statements)
1
14
0
Order By: Relevance
“…Within ophthalmic diseases, recent studies have shown that oral and systemic administration of the metal chelator deferiprone (DFP) is effective in ameliorating signs of retinal degeneration in transgenic mouse models of age-related macular degeneration [35, 36]. Combination free-radical scavenger/metal chelator compounds have been shown to mitigate retinal damage induced by light [37]. We have previously shown that chelation by EDTA-MSM is effective in reducing oxidative stress-induced toxicity in diabetic cataract and in an in vitro model of neurodegenerative disease [16, 38].…”
Section: Resultsmentioning
confidence: 99%
“…Within ophthalmic diseases, recent studies have shown that oral and systemic administration of the metal chelator deferiprone (DFP) is effective in ameliorating signs of retinal degeneration in transgenic mouse models of age-related macular degeneration [35, 36]. Combination free-radical scavenger/metal chelator compounds have been shown to mitigate retinal damage induced by light [37]. We have previously shown that chelation by EDTA-MSM is effective in reducing oxidative stress-induced toxicity in diabetic cataract and in an in vitro model of neurodegenerative disease [16, 38].…”
Section: Resultsmentioning
confidence: 99%
“…This study was conducted as previously described in detail. 35 Briefly, groups containing twelve 4-5-week-old male Wistar rats receiving either normal rat chow (untreated), normal rat chow and topically treated with Optixcare EH b.i.d., or an oral diet containing 0.05% of the multifunctional antioxidant JHX-4 as described above were dark adapted for 2 weeks. Rats from each group were then individually placed into acrylic, flat-bottom rodent restraints (Plas-Labs, Inc., Lansing, MI) in a light-box apparatus and exposed for 3 h to 1,000 lx of cool white fluorescent light (Lights of America, Los Angeles, CA; light-damaged rats, LD).…”
Section: Light-induced Retinal Damagementioning
confidence: 99%
“…10 Kador has synthesized novel multifunctional antioxidants with the ability to scavenge free radicals and chelate iron independently, and demonstrated that by oral administration, they both delay cataract formation and protect the retina against light damage, a model for AMD. [34][35][36] Based on the hypothesis that oral administration of antioxidants generally fail to achieve adequate levels of antioxidants to the lens, a topical nutraceutical suspension called Optixcare Eye Health (Optixcare EH) is being developed.…”
mentioning
confidence: 99%
“…Outside the area of oncology, an increasing number of publications supports the opinion that commonly used pharmaceuticals may provide a therapeutic benefit partially based on their antioxidant properties . Accordingly, oncology patients with co‐morbid conditions frequently incorporate such pharmaceuticals into their treatment.…”
mentioning
confidence: 99%